DIAGNOSTIC ACCURACY OF MULTIPARAMETRIC MRI IN DETECTING PROSTATE CANCER: A SYSTEMATIC REVIEW AND META-ANALYSIS COMPARED TO BIOPSY - MOHAMED EL GAZZAR, SAIF ALMAGHRABI, RYOOF SARHAN, DEMAH HAMDI AL SUFYANI, ASEEL MOHAMMED ALRADADI, AHMED HABIB HMED ALLUQMANI, ABDULRAHMAN MOHAMMED ALI; RUBA MAHMOUD ABDULLAH ALMUALLIM, MANAR ABOBAKR, FAISAL FALEH ALHARBI, RIMAA KHALID MAJAL ALQAHTANI, SARAH MOHAMMED AWADH ALQAHTANI, ASMA ALI ALSHAMRANI, ABDULLAH HASSAN AL HMOAD (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Background: Prostate cancer (PCa) remains one of the most prevalent malignancies among men worldwide, and accurate early detection is critical for optimizing treatment outcomes. Multiparametric MRI (mpMRI) has emerged as a non-invasive diagnostic tool that may improve sensitivity and reduce unnecessary biopsies. Objective To systematically review and meta-analyze the diagnostic accuracy of mpMRI for detecting prostate cancer compared with biopsy, including assessment of its role in detecting clinically significant disease. Methods A systematic review was conducted according to PRISMA 2020 guidelines. Databases searched included PubMed, Scopus, Web of Science, Embase, and Cochrane Library, covering studies published between 2010 and 2024. Sixteen eligible studies were included, encompassing prospective and retrospective cohorts, randomized controlled trials, and meta-analyses. Data extraction focused on sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and overall accuracy, with risk of bias assessed using the Newcastle–Ottawa Scale and Cochrane Risk of Bias tool. Results mpMRI demonstrated high sensitivity (often >85%) and excellent NPV (>90%) across included studies, particularly for clinically significant prostate cancer. Targeted biopsies guided by mpMRI outperformed systematic biopsies in diagnostic yield and reduced over-detection of indolent tumors. However, specificity varied widely (11–79%), and reduced visibility was noted for cribriform and intraductal carcinoma subtypes. Biparametric MRI (bpMRI) showed comparable accuracy in selected cohorts, with advantages in efficiency and cost. Conclusion: mpMRI provides a robust diagnostic modality for prostate cancer, improving detection of significant disease and reducing unnecessary biopsies. Variability in specificity and challenges with certain histological patterns remain, but mpMRI has the potential to reshape diagnostic pathways when integrated with targeted biopsy strategies. Future work should focus on optimizing protocols, validating bpMRI, and refining imaging for histologically aggressive subtypes.